Colloid and interface chemistry for nanotechnology - Kralchevsky, Peter A. (Boca Raton : Taylor & Francis, 2014)
'This book describes highlights in the very modern scientific world of nanotechnology. The contributions are all based on state-of-the-art principles in colloid and interface science and show how great progress in the various branches of nanotechnology can be reached. The chapters give examples of the synthesis of nanoparticles for specific applications as well as their characterization in bulk phases and at interfaces. The application of the colloid and interfacial science principles allows also developing new experimental and theoretical tools'--
Includes bibliographical references and index.
Keywords: Colloids; Surface chemistry; Nanoparticles